Mechanisms of quinolone resistance in a clinical isolate of Escherichia coli highly resistant to fluoroquinolones but susceptible to nalidixic acid. - Moniot-Ville, N (1991)
Two associated resistance mechanisms were found in a nalidixic acid-susceptible (4 micrograms/ml) but fluoroquinolone-resistant (8 to 16 micrograms/ml) strain of Escherichia coli Q2 selected under norfloxacin therapy. As compared with the susceptible E. coli Q1 isolated before treatment, changes in outer membrane proteins and lipopolysaccharides in Q2 were associated with a 1.5- to 3-fold decrease in the uptake of fluoroquinolones but not nalidixic acid. A 50% inhibition of DNA synthesis in toluene-permeabilized cells of the resistant strain E. coli Q2 required up to 500-fold increased quantities of fluoroquinolones, whereas such inhibition was obtained in both E. coli Q1 and Q2 with similar amounts of nalidixic acid. Selection from E. coli Q1 on norfloxacin of one-step resistant mutants resembling E. coli Q2 was unsuccessful. From these results we infer that a decrease in outer membrane permeability, associated with a peculiar alteration of the DNA gyrase, was responsible for the unusual quinolone resistance phenotype of E. coli Q2.